Influence of sleep patterns on hormonal regulation and metabolic biomarkers: A cross-sectional observational study - Banpur Rajini; Mudassir Mirza; Shareefa M; Syeda Samina (Asian Journal of Medical Sciences, 2023)
Background: Sleep duration and quality play a critical role in health, impacting hormonal regulation and metabolic functions. Aims and Objectives: This study aimed to investigate the complex interplay between sleep patterns, hormonal regulation, and metabolic biomarkers. Materials and Methods: A cross-sectional observational study was conducted involving 100 individuals. Demographically, participants averaged 35.2 years, with 45% males and 55% females and an average body mass index (BMI) of 25.9 kg/m² (ranging 18.7–32.5). Sleep assessment revealed an average duration of 7.2 h (range: 5.5–9.0 h) and a mean sleep quality score of 6.8 (range: 3–11). Results: Correlation analyses spotlighted significant associations between sleep duration and hormonal markers. Negative correlations emerged for cortisol and leptin, while insulin showed non-significance. Sleep duration exhibited both a positive correlation with fasting glucose and non-significant negative and positive correlations with total cholesterol and high-density lipoprotein cholesterol. Incorporating age, gender, and BMI, multivariate regression underscored sleep duration’s enduring impact on cortisol (Coefficient=−0.23, SE=0.09, P=0.021, 95% CI [−0.42, −0.04]). However, the sleep duration-fasting glucose relationship lost significance post-adjustment (Coefficient=0.09, SE=0.06, P=0.128, 95% CI [−0.03, 0.21]). Conclusion: This study illuminates intricate links between sleep, hormones, and metabolism. Sleep duration influences cortisol, and fasting glucose associations involve multifaceted factors. These insights offer direction for future research and clinical approaches in managing sleep-related health aspects.